Development of high throughput screening protocol and identification of novel sources of resistance against bakanae disease in rice (Oryza sativa L.) - Fiyaz, R. Abdul; Krishnan, S. Gopala; Rajashekara, H.; Bashyal, B. M.; Bhowmick, P. K.; Singh, N.K.; Prabhu, K.V.; Singh, A.K. (The Indian Journal of Genetics and Plant Breeding, 2016)
Bakanae or foot rot disease caused by Fusarium fujikuroi (teleomorph: Gibberella fujikuroi, Sawada,Wollenweber) is emerging as a serious disease of rice. A simple, reliable and high-throughput method for screening the disease would enable rapid screening of germplasm aimed at identifying resistance sources, mapping QTLs/genes and developing resistant rice cultivars. In the present study, a highthroughput, reliable bioassay to screen rice germplasm for resistance to bakanae disease was developed and compared with the conventional screening technique. This technique involves soaking of rice seeds in fungal spore suspension (1.0x106 spores ml–1) for 24 hours at room temperature. Seedling growth at 30°/25° (±3)°C day/night temperature and 60/80(±10)% day/night relative humidity in glasshouse gave the best results. The new protocol described here produces consistent and reproducible bakanae disease symptoms and enables screening of hundreds of rice germplasm within 15 days without any loss of precision in screening of rice genotypes against bakanae disease.The resistant and susceptible genotypes can be used for developing mapping population and identification of QTLs/genes conferring resistance to bakanae disease.